The Mechanism of Free Cash Flow and Financial Distress on Earnings Management Practices with Profitability as a Moderation Variable - Arief Prayogo; Lilis Ardini (LP2M IAIN Palopo, 2026)
This study examines the effect of free cash flow and financial distress on earnings management in energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. It also analyzes the role of profitability as a moderating variable that may strengthen or weaken the relationship between free cash flow, financial distress, and earnings management. This research uses a quantitative approach with secondary data obtained from companies' annual reports published by the IDX. The sample was selected using purposive sampling from companies that consistently published financial statements during the research period. Earnings management was measured using the Modified Jones Model through discretionary accruals, and the data were analyzed using multiple linear regression with a moderating interaction test. The results indicate that free cash flow and financial distress have a positive and significant effect on earnings management. Furthermore, profitability weakens the effect of free cash flow and financial distress on earnings management, indicating that higher profitability can reduce the tendency of management to manipulate financial information